An ESP Based Needs Analysis of English Subject for Room Division Students In A Hospitality Higher Education Context - Muh. Al Fachrizah Fitra; Sultan Baa; Samtidar Samtidar; Yunitari Mustikawati; Ulvah Sari (English Education Postgraduate Program, Universitas Negeri Manado, 2025)
This study investigates the English language needs of students enrolled in the Room Division program at the Tourism Polytechnic of Makassar Indonesia Recognizing English as a critical skill in the hospitality sector especially in guest facing roles this research aims to assess whether the current English course aligns with the communicative demands of the workplace Employing a sequential explanatory mixed methods design quantitative data were gathered through a 15 item Likert scale questionnaire administered to 39 students while qualitative insights were collected via semi structured interviews with four purposively selected participants Statistical analysis revealed that students perceived English as highly relevant to their future careers particularly in speaking and customer service contexts However they also expressed a need for more interactive learning including simulations role plays and authentic materials Thematic analysis of the interview data confirmed that students found the course lacking in real world communication practice and contextualized vocabulary Grounded in ESP theory this study identifies gaps between the current curriculum and the specific language tasks expected in hotel operations The findings underscore the importance of tailoring English instruction to meet learners professional goals and suggest the integration of task based industry relevant activities Recommendations are provided for curriculum developers instructors and policymakers to enhance the effectiveness of ESP instruction in vocational hospitality education < em>< p>